Aerodynamic performance and riding posture in road cycling and triathlon. (March 2015) - Barry, Nathan; Burton, David; Sheridan, John; Thompson, Mark; Brown, Nicholas AT
Cycling performance is strongly dependent on aerodynamic drag, of which the majority is attributable to the rider. Previous studies have shown the importance of optimising athlete posture on the bicycle for individual time-trial events. This article identifies that performance in road cycling and draft-legal triathlon can be improved through aerodynamic optimisation of the athlete's posture. Nine relevant cycling postures have been studied, and it was found that for road cycling, gripping the hoods with horizontal forearms can reduce the required cyclist power by 13.4%, and for draft-legal triathlon applications, the use of short bar extensions reduced the required power by up to 16.7%. It was also found that lowering the eyes and head increased drag in both drops and triathlon postures. Measurements of the velocity profiles of the wake of a cyclist in four different postures are presented, and it is shown that differences in drag coefficients between postures can be correlated with changes in the wake velocity defect and turbulence intensity distribution.